Pengaruh Kinerja Keuangan, Ukuran Perusahaan, dan CSR terhadap Harga Saham Pada Perusahaan Properti di Bursa Efek Indonesia 2018-2020 - Sholihah, Maratus; Susilo, Dwi Ermayanti (Institut Agama Islam Negeri (IAIN) Curup, 2021)
This study aims to determine the effect of financial performance, company size and Corporate Social Responsibility on stock prices in property companies listed on the IDX. The population used in this study are property companies listed on the Indonesia Stock Exchange in 2018-2020. The sample selection used a purposive sampling method with a total of 12 companies during 2018-2020. The data analysis technique uses multiple linear regression analysis with the SPSS (statistical package for social science) program for windows version 21. Based on the results of partial statistical analysis, it can be concluded that: 1) Financial Performance / Return On Equity (ROE) has no positive effect on stock prices, 2) Company Size has no negative effect on stock prices, 3) CSR there is no negative effect on stock prices in property companies listed on the IDX in 2018-2020 with a coefficient of determination of 0.048 this value means that 4.8% of stock prices during 2018-2020 are influenced by ROE, Size, and CSR while the remaining 95,2% share price is influenced by other variables